Artificial Olfactory Neuron for an In‐Sensor Neuromorphic Nose (Adv. Sci. 18/2022). Issue 18 (23rd June 2022) - Han, Joon‐Kyu; Kang, Mingu; Jeong, Jaeseok; Cho, Incheol; Yu, Ji‐Man; Yoon, Kuk‐Jin; Park, Inkyu; Choi, Yang‐Kyu
Abstract : Artificial Olfactory Neuron In article number 2106017 by Inkyu Park, Yang‐Kyu Choi, and co‐workers, a neuromorphic module of an electronic nose (E‐nose) is demonstrated by hybridizing a semiconductor metal oxide (SMO) gas sensor and a single transistor neuron (1T‐neuron). By mimicking a biological olfactory neuron, it can perform gas detection and spike encoding simultaneously for in‐sensor neuromorphic functioning. An electronic sommelier is implemented by classifying different types of wines.